Think for yourself restoring common sense in an age of experts and artificial intelligence - Mansharamani, Vikram (Gildan Audio, 2020)
At the height of the 2014 Ebola epidemic, a man who had recently returned from West Africa with a fever and severe abdominal pain entered a hospital in Dallas-and was sent home. Even after healthcare workers learned their patient had come from Liberia, ground zero of the Ebola hot zone, not one of those treating him considered the deadly virus as a possible cause of his condition. Shortly after the man died, one of the nurses who had treated him sought clearance from the Centers for Disease Control to board a commercial flight. She reported a fever of 99.5 degrees, but because the protocol restricted travel at 100.4 degrees or higher, she was cleared. She was later confirmed to be infected with Ebola.How could this happen' As Vikram Mansharamani shows in this eye-opening book, our complex, data-flooded world has made us ever more reliant on experts, protocols, and technology. We've stopped thinking for ourselves. (Have you ever followed your GPS device to a deserted parking lot')Of course, experts, protocols, and computer-based systems are essential to helping us make informed decisions. What we need is a new approach for integrating these information sources more effectively. The author provides principles and techniques for doing just that, empowering listeners with a more critical and nuanced approach to making decisions.
Downloadable audio file
Keywords: Business; Affaires; BUSINESS & ECONOMICS / General; Downloadable audio books; Audiobooks; Livres audio